Ice algae contributions to the benthos during a time of sea ice change: a review of supply, coupling, and fate - Niemi, Andrea; Bluhm, Bodil A.; Juul-Pedersen, Thomas; Kohlbach, Doreen; Reigstad, Marit; Søgaard, Dorte H.; Amiraux, Rémi (Frontiers in Environmental Science, 2024)
The polymer-facilitated flux of ice algae on Arctic shelves can initiate benthic activity and growth after the nutritionally constrained winter period. Lipid-rich ice algae are readily consumed by benthos and those entering the sediment can benefit deposit feeders. Ice algae assimilated by benthic organisms cascade up multiple trophic levels within the benthic sub-web, re-entering the pelagic sub web through habitat coupling species. Pelagic predators can have significant ice-algal carbon signals obtained from the benthic compartment. Sympagic-pelagic-benthic coupling on Arctic shelves is expected to weaken with ongoing sea-ice change. This review discusses the phenology, quantity, and quality of ice-algal contributions to coupling, linked to thinning snow and ice cover including multiyear ice replacement. Predicting future coupling between marine sub-webs requires focused research that considers trophic markers of multiple carbon sources.